The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s43545-022-00455-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Google Translate-friendly strategies for optimizing the quality of Google Translate in academic writing contexts

Abstract: The present study explored the types of errors found in Google Translate (GT) Chinese-to-English translations and, based on those error types, proposes strategies for optimizing the performance of GT. Seven abstracts written in both Chinese and English from seven articles published in English Teaching and Learning in 2017 were selected as the materials. The researchers compared the GT translations to the English abstracts written by the original author(s) and analyzed the problems in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…With the currently available machine translation technology, several methods can be employed to decrease the chance of errors, mostly requiring additional human input to assess the translation systems output. 37,38 Machine translation combined with the utilisation of the review team's knowledge may reduce the financial and resource burden of translation. The combination of both methods might reduce the inaccuracy of machine translation through manual checking while reducing the individual time burden on authors performing full translations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the currently available machine translation technology, several methods can be employed to decrease the chance of errors, mostly requiring additional human input to assess the translation systems output. 37,38 Machine translation combined with the utilisation of the review team's knowledge may reduce the financial and resource burden of translation. The combination of both methods might reduce the inaccuracy of machine translation through manual checking while reducing the individual time burden on authors performing full translations.…”
Section: Discussionmentioning
confidence: 99%
“…However, more testing and development is needed before it will be able to be widely utilised. With the currently available machine translation technology, several methods can be employed to decrease the chance of errors, mostly requiring additional human input to assess the translation systems output 37,38 . Machine translation combined with the utilisation of the review team's knowledge may reduce the financial and resource burden of translation.…”
Section: Discussionmentioning
confidence: 99%
“…This is caused by the factor of writing, which is the most complex skill in language, so it has the highest difficulty level. In the last ten years, several studies on writing have shown that writing strategies are essential in efforts to improve writing skills [4], [5], writing strategies [6], [7], [8], [9], [ 10], and writing motivation [11], [12], [13] which will influence other skill contexts, for example, reading or cognitive abilities. Writing is not easy because it requires complex skills and tenacity from the writer [14].…”
Section: Introductionmentioning
confidence: 99%